Collocation Analysis in Twelve Grade English Textbook - Sofi Yunianti; Idhoofiyatul Fatin; Sulton Dedi Wiajaya (Journal of English Language Teaching and English Linguistics, 2022)
Learning foreign language needs several ways. One of the ways is collocation. Collocation is considerably prominent in learning foreign language due to the influence in language comprehension. The high proficiency in collocation reflects high proficiency in foreign language comprehension. It is therefore this study aims to scrutinize the collocation which used in twelve grade English Textbook. this study applied corpus software, namely antconc. the first step for collecting the data, was changing the data from pdf to txt and process it in antcont for finding the top twenty wordlist. Then, find the top twenty sentences based on the lexical which find from wordlist. Based on the antcont process, the finding illustrates that only two types of collocation which occurred in twelve grade English textbook. It can be reflected that twelve grade English textbook limited provided collocation. Although, it is very crucial as learning material plays significant role in teaching learning process. As a result, this study is estimated to gain insight about in teaching English as foreign language, especially teaching media in textbook.